Landslide Susceptibility Evaluation Based on Empowerment Information Quantity Model of Game Theory - CUI Chengtao; LI Limin; FU Zhentao; REN Ruibin; WANG Lianxia; FENG Qingqing (Renmin Zhujiang)
In the process of employing information quantity models for landslide susceptibility zoning,given that the information quantity of influencing factors is directly added or multiplied by a single weight,without considering the main and objective weight of the factor,this paper proposes an evaluation method based on the empowerment information quantity model of game theory.First,the analytic hierarchy process (AHP) is adopted to calculate the subjective weight,the objective weight is determined by the coefficient of variation method,and then the game theory principle is utilized to optimize the main and objective weight to get the combination weight.Meanwhile,the information layer of each evaluation factor is weighted and summed based on the combination weight,and the evaluation results are divided into five categories by the natural intermittent point method.Finally,by taking Shanyang County of Shaanxi Province as the research area,the proposed model is compared with the information quantity model of single weight in landslide-susceptibility zoning maps,zoning point density,and ROC curves respectively.The results show that the accuracy and reliability of the proposed method outperform traditional weighted information measurement methods.